A highly potent and broadly accessible bispecific nanobody for the treatment of ebola virus infections - Bu, Fan; Ye, Gang; Morsheimer, Kimberly; Turner-Hubbard, Hailey; Eaton, Brett; Anantpadma, Manu; Bheemanapally, Khaggeswar; Tan, Chalet; Davey, Robert; Li, Fang (PLOS Pathogens, 2026)
Author summary Ebola virus (EBOV) remains a significant global health threat, with current treatments providing only modest survival benefits and limited accessibility due to their dependence on injection and cold-chain transport and storage. Here we developed a novel bispecific nanobody, Nanosota-EB1/EB2-Fc, which combines two nanobodies (single-domain antibodies) targeting distinct epitopes on the EBOV glycoprotein. Through intramolecular cooperativity, Nanosota-EB1/EB2-Fc inhibits glycoprotein function and evades the virus’s decoy mechanisms. A single dose showed strong therapeutic efficacy in EBOV-infected mice, including when administered at late stages of infection. Nanosota-EB1/EB2-Fc is also suitable for intranasal administration and exhibits high in vitro thermostability, enabling needle-free delivery and refrigeration-independent deployment. Together, these features position Nanosota-EB1/EB2-Fc as a highly potent and broadly accessible therapeutic candidate for future EBOV outbreaks.